The contribution of the broadcast media in Reputation Repair in Kenyan Healthcare Corporates - Odhiambo, Judy Apondi; Mberia, Dr. Hellen K. (IJRDO-Journal of Applied Science, 2015)
The overall effect of crises is damage to corporate reputation. Reputations are widelyrecognized as valuable, intangible asset. Reputation being a valuable asset to anorganization, when crises occur, there is need for reputation repair. One of the mostimportant stakeholders in reputation repair is the media. The broadcast media can be used tobuild or restore an organization’s reputation as well it can destroy the reputation of anorganization. However, many healthcare corporates have continued to ignore the importantcontributions that the media plays towards reputation repair. This study thus fills a researchgap on how the broadcast media can be used in reputation repair in Kenyan healthcarecorporates. The major objective to this study was to establish the impact of the broadcastmedia coverage in reputation management in Kenyan healthcare corporates. The study useda descriptive survey design which enabled the researcher to get a quantitative and aqualitative insight into the opinions and attitudes of the respondents in different environmentsthat could easily be compared. The population included PRO’s of healthcare corporates,Media practitioners, employees from different healthcare corporates and consumers ofhealthcare services. The researcher used stratified sampling to select 10 healthcarecorporates and thereafter selected 10 PRO’s; 30 employees of the corporates were selected through systematic sampling; 150 consumers of healthcare services were selected throughmulti-stage sampling while 10 broadcast media practitioners were selected through randomsampling giving a study population of 200. The data collected was then analysed by the useof the SPSS (Statistical Package for Social Sciences) package 17.0 and presented in tables,frequencies, pie charts and graphs. The study established that strategies used in reputationrepair are usually effective when the media highlights them in their coverage. The studytherefore concluded that broadcast media coverage indeed has an impact in reputationrepair.